A gestão patrimonial de infraestrutura em um sistema público de abastecimento de água – utilização de método probabilístico para estimativa de quebras - Costa, Matheus do Carmo (2022)
This paper addresses the evaluation of asset management techniques in a water supply system of an university in order to generate methodologies and operating standards in closed water supply systems aimed at reducing water losses: identification of pipes, analysis of the concept of infrastructure asset management (IAM), study of water losses, application of probabilistic methods to predict pipe breakage and observation of the impacts of losses in the water supply systems of the Federal University of Mato Grosso do Sul, Campus Cidade Universitária, located in Campo Grande, state of Mato Grosso do Sul, Brazil. Controlling losses in water supply systems is not just about being sustainable, but it translates into effective savings in financial resources for the system manager. Therefore, evaluating the application of loss control methodologies in large, closed public systems is an extremely important stud. For this purpose, losses identification techniques were used globally and locally, such as minimum water flow, comparison of water and sewage consumption and use of a geophone to refine the location. The survey and identification of the pipes in the study region was carried out, as well as the number of failures per identified pipe was counted. Thus, it was possible to use this information to predict pipe breakages with the aid of the probabilistic method called linear extension of the Yule process (LEYP), through the Baseform software. During the study, it was possible to observe a reduction of 58.58% in the total consumption of the studied supply system, between March and the beginning of 2020. It is also observed that there was a 29.29% reduction in annual consumption when compared to the year 2019 com 2020. Thus, it is possible to note that the application of a loss control methodology in water supply systems promotes the correct management of natural resources, through proper water management, in addition to imposing on the final consumer the reduction of consumption, increasing profit.